Optically-Boosted Planar IBC Solar Cells with Electrically-Harmless Photonic Nanocoatings - Santos, Ivan M. (2023)
Funding Information: This work received funding from the FCT (Fundação para a Ciência e Tecnologia, I.P.) under the projects TACIT (PTDC/NAN‐OPT/28837/2017) and FlexSolar (PTDC/CTM‐REF/1008/2020). The authors also acknowledge the support of the H2020 Solar‐ERANET program, which funded the development of the IBC cells within the framework of the BOBTANDEM project. M.A. and J.B. acknowledge funding by FCT‐MCTES through the grant BD/14557/2022. Publisher Copyright: © 2023 The Authors. Advanced Optical Materials published by Wiley-VCH GmbH.